Recent progress in carbon nanotubes support materials for Pt-based cathode catalysts in PEM fuel cells. (15th August 2022) - Ortiz-Herrera, J.C.; Cruz-Martínez, H.; Solorza-Feria, O.; Medina, D.I.
Abstract: Support materials have a significant impact on catalytic activity, stability, and performance of catalysts toward the oxygen reduction reaction (ORR). The properties of carbon-based materials have made them an excellent alternative for use as support for nanosized catalysts. Recently, carbon nanotubes (CNTs) have been explored as catalyst support materials, and their properties make them a promissory alternative. Furthermore, catalysts supported on CNTs exhibit higher resistance to electrochemical oxidation, better catalytic performance, and higher durability than catalysts supported on carbon black. In recent years, CNTs have acquired great relevance as catalysts support materials for ORR in acid media. This review addresses the most relevant studies on CNTs modification using methods such as functionalization, doping, and hybrid supports (CNTs-metal oxide) used as supports for Pt-based cathode catalysts in proton exchange membrane fuel cells. Highlights: The catalytic activity and stability of Pt-based nanoparticles supported on modified CNTs are analyzed. Doped and functionalized CNTs are good support materials of Pt-based nanoparticles for the ORR. Hybrid materials combining CNTs and metal oxides are good supports of Pt-based nanoparticles for the ORR. Pt-based nanoparticles supported on modified CNTs show higher catalytic activity than those supported on pristine CNTs.